ISM and ISPS Code Implementation: Stakeholder Perspectives on Indonesian Maritime Education Effectiveness - Giovanni Battista Puteri; Abdul Rochman (Yayasan Literasi Sains Indonesia, 2025)
This phenomenological study investigates the effectiveness of International Safety Management (ISM) and International Ship and Port Facility Security (ISPS) Code curricula within Indonesian maritime vocational education, examining the experiences of twenty-one stakeholders, including industry professionals and recent graduates. Using interpretive phenomenological analysis, the research reveals tensions between theoretical regulatory mastery and practical implementation competency. Participants showed excellent theoretical knowledge acquisition (4.25/5.0 effectiveness), but significant deficiencies appeared in crisis management readiness (2.85/5.0) and adaptive leadership development (2.95/5.0). The findings highlight a